2020
DOI: 10.5847/wjem.j.1920-8642.2020.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Admission delay is associated with worse surgical outcomes for elderly hip fracture patients: A retrospective observational study

Abstract: BACKGROUND: The influence of surgical delay on mortality and morbidity has been studied extensively among elderly hip fracture patients. However, most studies only focus on the timing of surgery when patients have already been hospitalized, without considering pre-admission waiting time. Therefore, the present study aims to explore the infl uence of admission delay on surgical outcomes. METHODS: In this retrospective study, we recorded admission timing and interval from admission to surgery for included patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Prolonged pre-admission waiting time worsens surgical outcome, pre-operative anxiety score, and depression [ 23 , 24 ]. Moreover, it may also result in post-operative complications, mortality and increased hospitalization stay, and catastrophic costs [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged pre-admission waiting time worsens surgical outcome, pre-operative anxiety score, and depression [ 23 , 24 ]. Moreover, it may also result in post-operative complications, mortality and increased hospitalization stay, and catastrophic costs [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies with larger sample sizes are required to confirm our findings. Second, we did not obtain some variables related to survival, such as body mass index [ 43 ], time from fracture to hospital admission [ 44 ]. These unadjusted potential confounding factors may influence the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…When patients sustain a hip fracture, they are forced to lie at in a bed and are either in pain or needing analgesic medications, which often have sideeffects. Previous study found that patients who received operation within 2 days after injury had lower inhospital mortality and had better outcomes [29][30][31]. In this study, we found the mean fracture to operation duration was 7.10 days in COVID-19 pandemic group, and 5.31 days in no COVID-19pandemic group, the difference between the two groups was about 2 days, and the incidence of postoperative medical conmplications and 3-month mortality was 21.90% and 5.20% for COVID-19 pandemic group compared to 12.53% and 3.22% for no COVID-19 pandemic group in patients ≥ 70 years with hip fracture following HA.…”
Section: Discussionmentioning
confidence: 99%